The influence of e-payment and e-commerce services on supply chain performance: Implications of open innovation and solutions for the digitalization of micro, small, and medium enterprises (MSMEs) in Indonesia - Alfonz Lawrenz Kilay; Bachtiar H. Simamora; Danang Pinardi Putra (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The digitalization of micro, small, and medium enterprises (MSMEs) is important, considering the many associated benefits. Indonesia, through the government's direction, has begun to develop digitalization through the introduction of e-payment and e-commerce services into MSME supply chains, but many challenges are still encountered. In this research, we measured the influence of the use of e-payment and e-commerce services on MSME supply chain performance, as well as suggesting open innovations and solutions to accelerate the digitization of MSMEs. We collected data from 164 MSMEs in Indonesia, then conducted multiple linear regression analysis, descriptive analysis of research indicators, and interviews and discussions with research experts. The results demonstrate that there exists a positive and significant influence of both e-payment and e-commerce service variables on the performance of MSME supply chains in Indonesia. We determine ten research indicators with low values, which thus pose an obstacle to the digitization of MSMEs, and their implications, in order of open innovation and solutions, are presented in order to assist MSME actors, the government, and related institutions in accelerating the digitalization of MSMEs in Indonesia.
Keywords: 650; digitalization solution; e-commerce services; e-payment services; micro small medium enterprises (MSMEs); open innovation; supply chain performance